2006
DOI: 10.3758/bf03193814
|View full text |Cite
|
Sign up to set email alerts
|

The nature of restructuring in insight: An individual-differences approach

Abstract: The insightful problem-solving process has been proposed to involve three main phases: an initial representation phase, in which the solver inappropriately represents the problem; an initial search through the faulty problem space that may lead to impasse; and a postimpasse restructuring phase. Some theories propose that the restructuring phase involves controlled search processes, whereas other theories propose that restructuring is achieved through the automatic redistribution of activation in long-term memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(144 citation statements)
references
References 18 publications
6
136
1
1
Order By: Relevance
“…13 Figural Fluency is itself a complex task which is not necessarily a pure measure of executive functioning and it may be that performance on that task also reflects at least some spontaneous non-executively loaded processes that lead to new directions of work in producing new patterns. Overall, the present results support the view that System 2 processes play a lesser role in insight problem solving than in non-insight tasks, reflecting a greater importance of automatic implicit processes in re-structuring as suggested by early Gestalt theorists (Maier, 1931) and more recently by spreading activation accounts (Ohlsson, 1992;Ash & Wiley, 2006 …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…13 Figural Fluency is itself a complex task which is not necessarily a pure measure of executive functioning and it may be that performance on that task also reflects at least some spontaneous non-executively loaded processes that lead to new directions of work in producing new patterns. Overall, the present results support the view that System 2 processes play a lesser role in insight problem solving than in non-insight tasks, reflecting a greater importance of automatic implicit processes in re-structuring as suggested by early Gestalt theorists (Maier, 1931) and more recently by spreading activation accounts (Ohlsson, 1992;Ash & Wiley, 2006 …”
Section: Discussionsupporting
confidence: 79%
“…Fleck concluded that these results supported the spontaneous theory of restructuring in insight, i.e., relatively small role for System 2 and a larger role for System 1 processes in insight v. non-insight problem solving. Ash and Wiley (2006) contrasted insight problems with large and small search spaces and found that individual differences in ability to control attention (as indicated by working memory spans) was not associated with solving small space insight problems but was associated with solution of larger space problems. The results were interpreted as supporting automatic (System 1) accounts of restructuring.…”
Section: Dual Process Approaches and Insightmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Ohlsson's model (1992, p. 20) incorporates search as a necessary process before an impasse is met, the framework mainly focuses on what processes occur to release the problem solver from impasse, without a great deal of elaboration on the particular nature of search processes before Nine-dot problem 4 and after an impasse. Jones (2003) provided a model that elaborated Ohlsson's notion that insight problem solving can be understood as a sequential process of different phases (search -impasse -insight -search, see also Ash & Wiley, 2006). This model suggests that there might be a concerted interplay of search and impasse, with each affecting the other.…”
Section: Introductionmentioning
confidence: 96%